Acute oral toxicity and biodistribution study of zinc aluminium-levodopa nanocomposite - Kura, Aminu Umar; Saifullah, Bullo; Cheah, Pike See; Hussein, Mohd. Zobir; Azmi, Norazrina; Fakurazi, Sharida (SpringerOpen, 2015)
Layered double hydroxide (LDH) is an inorganic-organic nano-layered material that harbours drug between its two-layered sheets, forming a sandwich-like structure. It is attracting a great deal of attention as an alternative drug delivery (nanodelivery) system in the field of pharmacology due to their relative low toxic potential. The production of these nanodelivery systems, aimed at improving human health through decrease toxicity, targeted delivery of the active compound to areas of interest with sustained release ability. In this study, we administered zinc-aluminium-LDH-levodopa nanocomposite (ZAL) and zinc-aluminium nanocomposite (ZA) to Sprague Dawley rats to evaluate for acute oral toxicity following OECD guidelines. The oral administration of ZAL and ZA at a limit dose of 2,000 mg/kg produced neither mortality nor acute toxic signs throughout 14 days of the observation. The percentage of body weight gain of the animals showed no significant difference between control and treatment groups. Animal from the two treated groups gained weight continuously over the study period, which was shown to be significantly higher than the weight at the beginning of the study (P < 0.05). Biochemical analysis of animal serum showed no significant difference between rats treated with ZAL, ZA and controls. There was no gross lesion or histopathological changes observed in vital organs of the rats. The results suggested that ZAL and ZA at 2,000 mg/kg body weight in rats do not induce acute toxicity in the animals. Elemental analysis of tissues of treated animals demonstrated the wider distribution of the nanocomposite including the brain. In summary, findings of acute toxicity tests in this study suggest that zinc-aluminium nanocomposite intercalated with and the un-intercalated were safe when administered orally in animal models for short periods of time. It also highlighted the potential distribution ability of Tween-80 coated nanocomposite after oral administration.